2023
DOI: 10.3390/ani13152536
|View full text |Cite
|
Sign up to set email alerts
|

The Food Niche Overlap and Interspecific Relationship between the Sympatric Tibetan Macaque and Grey Snub-Nosed Monkey

Abstract: Assessing the trophic niche and interspecific relationships between related species and determining how the species maintain differences in nutritional niches while coexisting in the same area are important topics in ecological research. Therefore, exploring the mechanism of food resource utilization, competition and coexistence among species distributed in the same region is important. In this study, we used fecal samples and metagenome sequencing technology to study the plant feeding habits and coexistence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…We found that the top-ranked abundances of Magnoliaceae, Theaceae, Rosaceae, Viburnum, Cornus, and Nyssaceae have all been reported in previous R. brelichi dietary studies by traditional dietary analysis methods (Niu et al, 2014;Xiang et al, 2012;Yang et al, 2010). Eurya, Magnolia, Rubus and Morinda were reported to be present in the R. brelichi diet by DNA metabarcoding (Yue et al, 2023). In this study, Magnoliaceae was the top-ranked family in terms of the abundance of plant food species in R. brelichi, with a relative abundance of approximately 40%.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We found that the top-ranked abundances of Magnoliaceae, Theaceae, Rosaceae, Viburnum, Cornus, and Nyssaceae have all been reported in previous R. brelichi dietary studies by traditional dietary analysis methods (Niu et al, 2014;Xiang et al, 2012;Yang et al, 2010). Eurya, Magnolia, Rubus and Morinda were reported to be present in the R. brelichi diet by DNA metabarcoding (Yue et al, 2023). In this study, Magnoliaceae was the top-ranked family in terms of the abundance of plant food species in R. brelichi, with a relative abundance of approximately 40%.…”
Section: Discussionmentioning
confidence: 65%
“…Lyke et al (2019) reported ecological niche differences in the dietary arthropods of blue-and red-tailed monkeys. DNA metabarcoding has also been reported in studies of colobine in plant diets, such as R. brelichi (Yue et al, 2023), Presbytis femoralis (Srivathsan et al, 2016) and Pygathrix nemaeus (Srivathsan et al, 2015). Collecting faeces does not involve coming into direct contact with the rare R. brelichi and does not affect their behavioural activities.…”
Section: Introductionmentioning
confidence: 96%